The effect of specialized exercises on some motor abilities and improving the performance of the Kick to handstand on the beam apparatus in artistic gymnastics - سعدي , علي; ابراهيم , ندى; سعيد , وجدان (Journal of Sport Science Technology and Physical Activities, 2025)
The study aims to identify the effect of the proposed specialized exercises on some motor abilities and improve the performance of the skill of kicking to the handstand on the crossbar device in artistic gymnastics and for this purpose we used the experimental approach (by designing one group on a sample consisting of 6 players were deliberately selected and to collect data we used motor and skill tests and after collecting the results and processing them statistically was reached. that specialized exercises have influenced. In some motor abilities and improve the performance of the skill of kicking to stand on the hands and on This basis recommended additional research targeting other skills